Ukraine At The Fulcrum: A Nuclear House Of Cards - Natalie Manaeva Rice; Dean P Rice; Howard L Hall (International Journal of Nuclear Security, 2015)
The foundation of preserving and enhancing global nuclear security rests on three fundamental pillars: nuclear disarmament; preventing further proliferation of nuclear weapons; and international cooperation aimed at safeguarding nuclear materials. Today, experts argue that the recent decision of Russian president Vladimir Putin to cut cooperative efforts to secure nuclear materials are placing in peril the future of international efforts to promote global nuclear security. We argue that in addition to the clear erosion of the third pillar of nuclear security, there are more threatening ramifications resulting from the recent actions of Russia in Ukraine. The aggressive actions of Russia in Ukraine, together with the unwillingness of the international community to exert sufficient pressure on Russia to honor the promises made to Ukraine in exchange for giving up nuclear weapons in 1990s (the Budapest Memorandum) are detrimental to non-proliferation objectives and reach far beyond the geographic boundaries of the current conflict. In addition, they may disrupt both further nuclear disarmament and stimulate proliferation of nuclear weapons. To the government of any country who has resisted the push toward nuclearization based on trust placed in international agreements, the inactions and/or inability of the international community to resist or reverse Russia’s illegal actions must cause great concern. If binding diplomatic agreements are seen to only bind one party – the weaker party – that party will understandably be very hesitant to place full faith in any diplomatic document short of a binding treaty that has clear and required enforcement mechanisms. This is especially true when the stakes are a country’s national security and ultimately its sovereignty. If any one of these nations moved toward nuclear status, the atomic dominos would surely begin to tumble, and the delicate nuclear equilibrium that defines the global nuclear security landscape today would be lost.
Keywords: Ukraine; Russia; Budapest Memorandum; NPT; Nuclear Nonproliferation Treaty; Nuclear Proliferation; Putin; Nuclear Security